Reperfusion haemorrhage as determined by cardiovascular MRI is a predictor of adverse left ventricular remodelling and markers of late arrhythmic risk. Issue 6 (4th November 2010) - Mather, Adam N; Fairbairn, Timothy A; Ball, Stephen G; Greenwood, John P; Plein, Sven
Abstract : Background: Interstitial haemorrhage due to reperfusion of severely ischaemic myocardium can be detected in vivo by T2-weighted (T2W) and T2* cardiovascular magnetic resonance (CMR). The clinical implications of myocardial haemorrhage following primary percutaneous coronary intervention (PPCI) remain undetermined. Objectives: To assess whether the presence of myocardial haemorrhage influences ventricular remodelling and risk of late ventricular arrhythmia following PPCI for acute myocardial infarction (AMI). Methods: Forty-eight patients with first ST-elevation AMI, treated successfully with PPCI, underwent CMR at day 2 and 3 months. Left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV) and left ventricular ejection fraction (LVEF) were determined from cine-CMR, infarct size and microvascular obstruction (MVO) from gadolinium-enhanced images and area at risk (AAR) from T2W CMR. Myocardial haemorrhage was defined as hypointense signal within the AAR on both T2W and T2* images. All patients had a signal-averaged electrocardiogram at 3 months. Results: 30/48 (63%) patients had MVO and 12 of these showed myocardial haemorrhage. Patients with haemorrhagic myocardial infarction (MI) had significantly larger LVEDV and LVESV, lower LVEF and larger infarcts than those with non-haemorrhagic MI at baseline and at 3 months. The presence of haemorrhage was an independent predictor of adverse remodelling defined as increased LVESV on follow-up (p=0.001, OR 1.6) and prolonged filtered QRS (fQRS) on signal-averaged ECG at 3 months (p=0.020, OR 1.176). Conclusions: Reperfusion haemorrhage following AMI is associated with larger infarct size, diminished myocardial salvage and lower LVEF. The presence of haemorrhage is the strongest independent predictor of adverse ventricular remodelling and is also associated with prolonged fQRS duration, which is a marker of arrhythmic risk.